Hepatosplenic T-cell lymphoma in a young immunocompetent man - Petrova, Maja (BMJ Case Rep, 2016)
Hepatosplenic T-cell lymphoma (HSTCL) is a rare, aggressive type of peripheral T-cell lymphoma that is characterised by extranodal disease, with infiltration and proliferation of malignant T-cells within the liver, spleen and bone marrow. The authors report the case of a young immunocompetent man, who was admitted to the hospital with a history of prolonged, unexplained fever, fatigue and weight loss. Initial blood work showed mild pancytopaenia and imaging studies revealed hepatosplenomegaly. The diagnosis was challenging, initially mimicking infectious disease, and it required an extensive investigation that ultimately revealed the characteristic clinical, histopathological and cytogenetic features of HSTCL. The clinical course was aggressive, and despite multiagent chemotherapy, the patient died 4 months after the diagnosis. This case highlights the difficulty of diagnosing HSTCL and the importance of considering it in a differential diagnosis of hepatosplenomegaly in young men who present with constitutional symptoms and no lymphadenopathy.